Kendala dan Dukungan dalam Pembiayaan Pendidikan Mahasiswa Program Studi PIAUD UINSI Samarinda - Saugi, Wildan; AF, Abd. Rachim; Haryaka, Usfandi (Borneo Journal of Islamic Education, 2025)
This study aims to identify obstacles and support in financing education faced by students of the PIAUD Study Program at UINSI Samarinda. Although the number of students is increasing, significant financial challenges hinder their learning process and academic motivation. Qualitative methods were used to explore students' subjective experiences through in-depth interviews with 19 purposively selected participants. The selection of participants was based on students who had sources of financing from parents, scholarships, independent financing, and a combination of parental and scholarship costs, which included students in semesters 1, 3, 5, and 7. The findings showed that the main obstacles consisted of high dependence on parents, minimal information about scholarships, and application procedures that were considered complicated and non-transparent. These obstacles have an impact on difficulties in meeting tuition fees and accessing the necessary academic facilities. However, support through scholarship programs provides financial relief and is a key factor in supporting the sustainability of student studies. This study recommends improvements in the socialization of information about financing programs, simplification of scholarship application procedures, and development of more alternative financial assistance to support students in facing the challenges of financing education.